2008
DOI: 10.1063/1.2959730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indium on phase-change characteristics and local chemical states of In–Ge–Sb–Te alloys

Abstract: We introduce single-phase In–Ge–Sb–Te (IGST) quaternary thin film (fcc structure when crystallized) deposited by cosputtering from Ge2Sb2Te5(GST) and In3Sb1Te2 targets. This film, compared with the GST ternary system, provides a significant increase of amorphous-to-crystalline transformation temperature. High-resolution x-ray photoelectron spectroscopy (HRXPS) revealed that, with increasing In amounts, the Sb 4d and Ge 3d core peaks shift toward lower binding energies (BEs), with negligible changes in spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In addition, the IST is already known as optical data storage material 14. Furthermore, in a recent study, it is revealed that the IST–GST system shows a high phase change temperature compared with that of the GST system 15. Therefore, it is necessary to investigate the possibility of the IST ternary alloys for application in PRAM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the IST is already known as optical data storage material 14. Furthermore, in a recent study, it is revealed that the IST–GST system shows a high phase change temperature compared with that of the GST system 15. Therefore, it is necessary to investigate the possibility of the IST ternary alloys for application in PRAM.…”
Section: Introductionmentioning
confidence: 99%
“…The aim, to improve its characteristics for technological applications and also to understand the factors leading to the observed behavior, has sparked an interest into its substituted or doped variants. Previously, properties of several differently doped or substituted GST materials have been investigated both experimentally and theoretically. In this paper we focus on nitrogen doped GST.…”
Section: Introductionmentioning
confidence: 99%
“…1. 13 In the figure, the BE separations between the peaks of the Ga 3d and Zn 3d orbitals and the In 4d and Zn 3d orbitals are represented by "A" and "B," respectively. 10 ͑Ga 2 O 3 :In 2 O 3 :ZnO=1:1:1͒ for different ion-sputtering conditions.…”
Section: Ga 3dmentioning
confidence: 99%